Enhancing E-Government Proactive Services Through Advanced Data Processing Technologies - Herrera, Jose (European Scientific Journal, ESJ, 2024)
The approach of citizen to digital world allows to public sector provide services crossing frontiers of traditional relationships citizen-administration. Anticipate to consumer needs, approach to a more satisfaction relationship and reduce resolution time, are some of the goals for a new era of electronic public sector services. We compile a reduced set of proactive systems to illustrate and analyse options. The main goal of this paper is analysing the key role of Big Data and Digital Twin in public administrations as tools for provide ProActive Services (PAS). It Is common in government administration consider the use of disruptive technologies to increase services created to improve relationships with citizens. This document explores the use of innovative technologies to raise the number of proactive services running on public administration (Proactive Public Services - PPS), challenges it faces and technical limits that appear. A change in mindset must be done. Paraphrasing an illustrious United States president in inaugural address “Ask not what citizens do for administration – ask what administration can do for its citizens.”